Wild weather : storms, meteorology, and climate - Reed, M. K. (Science comics (First Second (Firm)), 2019)
A "snowpocalypse" descends and one newscaster makes a gaffe about climate change being a myth. Norman, a quirky meteorologist is frustrated with the lack of understanding and goes on to explain to the hapless newscaster the science behind meteorology, storms, climate, and weather phenomena.